Intraperitoneal Mouse Virulence of Salmonella typhimurium Hybrids Expressing Somatic Antigen 9 - Johnson, E. M. (1974)
Salmonella typhimurium hybrids expressing somatic antigen 9 after mating with either S. typhosa or S. enteritidis Hfr donors did not differ from their S. typhimurium parent with respect to the number of organisms required to produce death in mice inoculated intraperitoneally.